Komplikasi tindik lidah pada rongga mulut - Ali Yusran; Eddy Parinding (Journal of Dentomaxillofacial Science, 2008)
Historically, wearing adornments on pierced on body parts has been associated withmany cultures as manifestations of religious or cultural identities. Currently, its usehas a broad acceptance among young people. The most common sites for piercings arethe tongue and lower lip in the oral cavity. Several complications may be associatedwith this practice with the most frequently observed being halitosis, periodontitis,tooth fracture, glossitis, and the formation of abscesses. This paper was a case reportof patient who had a complication from piercing on the tongue located under theoverlying mucosa. It was suggested that a local habit was a possible initiator of thiscomplication.